Economic feasibility of producing pasta in Kenya - Warui, George (Kansas State University, 2018)
Between the years 2008 and 2017, pasta imports in Kenya grew at a rate of 16.12%. This is from data obtained from Kenya National Bureau of Statistics. Growth is projected to continue and can be attributed to factors such as population growth which grew from 38 million to 50 million for that period of time. This population is projected to keep growing and double by the year 2050. GDP per capita grew 58% from US$ 916 to US$ 1,455 between the years 2008 to 2016. This has resulted to growth of middle-class families and increased their purchasing power. Changing lifestyles has led to increased number of dual-income families where both husband and wife work, creating food habits that call for fast and convenient foods. Without domestic production, Kenya imports all its pasta. With the increased demand, it might be the right time for import substitution. This research seeks to find out if it is economically feasible to commercially produce and market pasta in Kenya. The research begins by simulating investment in a small scale pasta production plant in Kenya, followed assessing costs and revenues expected in the seven-year life of the investment. It involves starting up the plant, producing, marketing, and distributing the resulting pasta goods. It is funded through a Kenyan Shilling (Ksh.) 12 million loan from a local bank, payable in seven years at a 14% interest rate. From costs and revenues projections, cash flows are determined. The project’s feasibility is determined by evaluating the cash flows using both Net Present Value (NPV) and Internal Rate of Return (IRR) methods. Using the NPV method, the project has a positive NPV of Ksh.1,286,282.00. When using the IRR method it has an IRR of 45% which is above the cost of capital. It is concluded that the project is feasible. It is also noted that both semolina cost (main pasta production raw), and pasta sales price are important feasibility drivers. NPV’s sensitivity to both is therefore determined. From the analysis, the project remains feasible at all proposed pasta sales prices, as long as semolina cost does not exceed Ksh.56/Kilogram.
Keywords: Kenya; Pasta; Production; Import substitution